Neolithic, Copper, and Bronze Age woodland composition and exploitation in the Great Hungarian Plain, East‐Central Europe - Gabriella Darabos; Máté Róbert Merkl; Pál Raczky; András Füzesi; Attila Gyucha; Danielle J. Riebe; William A. Parkinson; Magdalena Moskal-del-Hoyo; Szilvia Fábián; Karola Molnár; Gabriella Hajdrik; Tamás Hajdu; et al. (Quaternary Environments and Humans)
In the prehistoric communities of the Great Hungarian Plain (GHP), the exploitation of forest steppe and floodplain woodlands started at ∼6000 cal BC. So far, only scattered and irregular wood charcoal analyses have been performed on Holocene archaeological sites, therefore the species composition of the GHP woodlands is known mainly from pollen records. This study aims to fill this gap by systematic sampling and analysis of key Early, Middle and Late Neolithic, and Copper and Middle Bronze Age archaeological sites. Pollen records from the vicinity of some archaeological sites accompany the charcoal assemblages along with potential vegetation and soil maps. Our results show that oak (Quercus sp.) was dominant in the floodplain and forest steppe, used as construction timber and firewood. Both high and low floodplain forest woody elements (Populus, Salix, Fraxinus) were represented. Elm species (Ulmus spp.) were widespread and often co-dominated the charcoal assemblages. In the long-term charcoal assemblages of the Late Neolithic SE GHP, Ulmus was more frequent than in the NE GHP. Soil and potential vegetation maps of these sites show meadow soil predominance with occasional chernozem meadow soils. Floodplain woodlands predominate in the potential vegetation with the likely presence of U. laevis and U. minor today corroborating the predominance of alluvial forests in SE Hungary during the Neolithic likely with high amplitude water table fluctuation. During the Early Chalcolithic (4500–4000 cal BC), we found a significant decline in Ulmus in the SE GHP both in the pollen and charcoal assemblages suggesting a climate change and/or pathogen induced elm-decline. In comparison with the Balkan region, we demonstrated that the SE border of the GHP was a major environmental barrier, north of which vast riparian and alluvial forests were alternating with steppe oak woods. The Early Neolithic communities had to adapt to this environment.